FEATURES OF EXTERNAL ENVIRONMENTAL DESIGN IN THE CONDITIONS OF REVITALIZATION OF THE INDUSTRIAL COMPLEX - Бурлак, Г. М.; Вілінська, Л. М. (Art and Design, 2021)
Purpose: analyze the experience of revitalizing an industrial complex in the context of creating an architectural space by means of external environmental design. Methodology. General scientific methods of analysis, comparative method, typological systematization, figurative and stylistic method, method of visual observation are applied. Results. The experience of revitalization of an industrial complex and the adjacent territory is considered on the example of the Waltrovka architectural space in Prague, Czech Republic. The figurative and semantic accents and architectural and artistic solutions for the revitalization of industrial complexes to create a modern ecologically, psychologically comfortable, socially oriented external environment are analyzed. The structural elements of the formation of new spaces in the place of industrial objects are highlighted. The constituent elements of the Waltrovka space can be viewed as urban planning objects integrated into the landscape component and the overall ecological system. Landscape solutions are characterized by harmony, diversity, use of functional and decorative design elements. The historical past of the industrial complex manifests itself in the preservation of old buildings and the use of art objects. Scientific novelty. The content and significance of the external environment design in the revitalization of an industrial complex with a complete change in functions and the disclosure of new possibilities of old territories and buildings of the Waltrovka architectural space has been determined. Practical significance. The results of the study can be used in the practice of design of the external environment and landscape design during the revitalization of industrial areas to preserve historical significance.